PENGARUH TERAPI MUSIK TERHADAP KEMAMPUAN BERSOSIALISASI PADA PASIEN ISOLASI SOSIAL DI RUMAH SAKIT UMUM DAERAH MADANI PROVINSI SULAWESI TENGAH - Salamung, Niswa; Elmiyanti, Ni Ketut; Purwaningsih, Diah Fitri; Lating, Desmini (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
Introduction: Social isolation is a condition where a person cannot interact with other people and does not want to socialize with other people. Based on the results of observations made on 4 social isolation patients who were in the Manggis, Salak and Serikaya rooms, it showed that the patients were unable to socialize, rarely did music therapy, the social isolation patients did not know what therapy could be done to improve social skills and did not know the purpose of the therapy. music. The aim of this research is to determine the effect of music therapy on the ability to socialize in socially isolated patients at the Madani Regional General Hospital, Central Sulawesi Province. Method: This type of research is quantitative with a pre-experiment design with a pre test-post test one group only design. Data types are primary and secondary. Data were analyzed univariately and bivariately using the Wilcoxon Signed Ranks Test. The population in this study were all social isolation patients in the Manggis, Salak and Serikaya rooms. The sample in this study consisted of 10 respondents, using total sampling. Results: The results of the study showed that the statistical test results obtained a p value = 0.005 ≤ 0.05, with a median value before music therapy of 2, maximum and minimum values of 1-7, while the median value after music therapy was 8, maximum and minimum values by 3-10. The conclusion is that there is an influence of music therapy on social skills in social isolation patients. Suggestions It is hoped that this research can be used as a reference in the library in developing knowledge about nursing and for administrators in the Manggis, Salak and Serikaya rooms, it is hoped that they can apply the therapy that has been carried out as a permanent activity schedule for social isolation patients to improve social skills.